2019
DOI: 10.1055/s-0039-1692964
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Language, Executive Function, and Intervention in Autism Spectrum Disorder

Abstract: Difficulties with both executive functions and language skills are common but variable in autism spectrum disorder (ASD). Executive functions and language skills are related to one another, such that vocabulary, syntax, and pragmatics are related to domains of working memory, shifting, and inhibition in ASD, although the directionality of these relationships remains unclear. Moreover, interventions that target pragmatic ability have been found to improve executive function skills, and conversely, executive fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 66 publications
(146 reference statements)
4
50
0
4
Order By: Relevance
“…This theory also purported to account for theory of mind deficits within ASC, as EF difficulties would make it harder for a subject to simultaneously hold two representations in mind, i.e., one about reality and the other about the other person's representation of reality. Overall, a recent meta-analysis of EF in ASC confirms a broad executive dysfunction (Demetriou et al, 2018), although EF deficits are not currently regarded as core symptoms of ASC (Friedman and Sterling, 2019).…”
Section: Executive Function and Inner Speech In Ascmentioning
confidence: 98%
See 3 more Smart Citations
“…This theory also purported to account for theory of mind deficits within ASC, as EF difficulties would make it harder for a subject to simultaneously hold two representations in mind, i.e., one about reality and the other about the other person's representation of reality. Overall, a recent meta-analysis of EF in ASC confirms a broad executive dysfunction (Demetriou et al, 2018), although EF deficits are not currently regarded as core symptoms of ASC (Friedman and Sterling, 2019).…”
Section: Executive Function and Inner Speech In Ascmentioning
confidence: 98%
“…However, experimental research on EF has been said to suffer from the so-called "task impurity problem" (Snyder et al, 2015), which appears when the administration of a certain task prompts the use of several different cognitive processes within the whole construct, thus leading to potentially conflated results regarding specific EFs (e.g., a subject's score on the WCST might depend on the recruitment of task-switching, planning, and working memory: Geurts et al, 2009). 2 The different components of EF are related to different areas in the brain (Vivanti et al, 2019) and may even belong to different "systems" or ways of processing information (Friedman and Sterling, 2019). Several researchers distinguish between core EF and higher-order EF as follows:…”
Section: Executive Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported WM deficits in ASD relative to typically developing (TD) populations (Barendse et al 2013). Although a number have reported primarily visuo-spatial WM impairment, with verbal WM being relatively intact in individuals with ASD (Boucher et al 2008;Minshew et al 2001;Steele et al 2007), more recent papers also find verbal WM difficulties (e.g., Friedman et al 2019). Visual WM has been shown, however, to be a sensitive marker of developmental disability (Alloway et al 2016).…”
Section: Behavioural Studies Of Working Memory In Asdmentioning
confidence: 99%